2021
DOI: 10.3390/nu13103534
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diets in India: Gaps, Barriers, and Opportunities

Abstract: Suboptimal dietary intake is a critical cause of poor maternal nutrition, with several adverse consequences both for mothers and for their children. This study aimed to (1) assess maternal dietary patterns in India; (2) examine enablers and barriers in adopting recommended diets; (3) review current policy and program strategies to improve dietary intakes. We used mixed methods, including empirical analysis, compiling data from available national and subnational surveys, and reviewing literature, policy, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…11 Education is a crucial part of prenatal care, but previous research has shown that women anticipate getting more nutrition advice from their doctor, midwife, or other healthcare than they do. 8 In our survey, healthcare professionals confirmed that they communicate the importance of nutrients via counselling, diet chart, videos and handouts. Nevertheless, this survey provides encouraging results to disseminate the importance of supplements in pregnancy and increase the use of DHA consumption in pregnant women and shows the need for appropriate guidelines for prescribing the supplements.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…11 Education is a crucial part of prenatal care, but previous research has shown that women anticipate getting more nutrition advice from their doctor, midwife, or other healthcare than they do. 8 In our survey, healthcare professionals confirmed that they communicate the importance of nutrients via counselling, diet chart, videos and handouts. Nevertheless, this survey provides encouraging results to disseminate the importance of supplements in pregnancy and increase the use of DHA consumption in pregnant women and shows the need for appropriate guidelines for prescribing the supplements.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, it is imperative to start with DHA supplementation from the first trimester and up to 18 months of life. [6][7][8] The majority of HCPs prescribe a dose of 400 mg followed by 200 mg. 5 A survey conducted in the USA from 2003-2014 to evaluate the n-3 FA intake concluded that the estimated intakes of n-3 FA in pregnant women did not differ from non-pregnant women (100.6 versus 92.7 mg EPA+DHA in pregnant versus non-pregnant women aged 20-44 years). The estimated EPA+DHA intake by pregnant women is Prescriber % less than one-fifth of the required 520 mg/day of EPA+DHA for pregnant and lactating women, as recommended by the Workshop on the Essentiality of and Recommended Dietary Intakes recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest diet diversity is found in the western part of India, whereas the southern-costal and eastern-costal parts of India have reported higher diet diversity (as in Fig 2A). Several factors, such as geographical availability of foods [48][49][50][51][52], accessibility to markets, purchasing capacity [53,54], level of education, individual tests, and preferences [55], etc., are the significant determinants of dietary diversity at the regional level in India [56,57]. PLOS GLOBAL PUBLIC HEALTH…”
Section: Discussionmentioning
confidence: 99%
“…Maternal diet is carefully managed, food is prepared fresh and no processed foods are generally used. However, despite a variety of government policies, 65–75% of households could not afford a wholesome nutritious diet, which is usually poor in iron and other micronutrients, and many women suffer from anaemia 49 . In many urban areas in India, maternal obesity is increasing and may impact the incidence of atopic and allergy diseases in newborns 50,51 .…”
Section: Food Allergy Risk Factors and Their Likely Influence On The ...mentioning
confidence: 99%